Financial Literacy, Financial Planning, Financial Management: An Analysis of Intergenerational Behavior in Gen-X, Gen-Y and Gen-Z - Christian, Adhitya Rechandy; Sukardi; Bidayati, Utik (Journal of Management Studies and Development, 2025)
This study investigates intergenerational differences in financial literacy, financial planning, and financial management among residents of Yogyakarta. The research sample comprised individuals from Gen-X, Gen-Y, and Gen-Z, with 60 respondents representing each generational cohort. A simple random sampling technique was employed, and the Kruskal-Wallis test was utilized to analyze the data. The findings reveal no statistically significant differences in financial literacy and financial planning across the three generations. However, significant generational differences were identified in financial management practices. Notably, Gen-Z demonstrated superior financial management behavior compared to both Gen-X and Gen-Y.